Adjuvant statin therapy for oesophageal adenocarcinoma: the STAT‐ROC feasibility study. Issue 1 (3rd February 2020) - Alexandre, L.; Clark, A. B.; Walton, S.; Lewis, M. P.; Kumar, B.; Cheong, E. C.; Warren, H.; Kadirkamanathan, S. S.; Parsons, S. L.; Dresner, S. M.; Sims, E.; Jones, M.; et al.
Graphical Abstract: Abstract: Background: Statins inhibit proliferative signalling in oesophageal adenocarcinoma (OAC) and their use is associated with better survival in observational studies. The present study was undertaken to examine the feasibility of assessing adjuvant statin therapy in patients with operable OAC in a phase III RCT. Methods: For this multicentre, double-blind, parallel-group, randomized, placebo-controlled feasibility trial, adults with OAC (including Siewert I–II lesions) who had undergone oesophagectomy were centrally allocated (1 : 1) to simvastatin 40 mg or matching placebo by block randomization, stratified by centre. Participants, clinicians and investigators were blinded to treatment allocation. Patients received treatment for up to 1 year. Feasibility outcomes were recruitment, retention, drug absorption, adherence, safety, quality of life, generalizability and survival. Results: A total of 120 patients were assessed for eligibility at four centres, of whom 32 (26·7 per cent) were randomized, 16 in each group. Seven patients withdrew. Participants allocated to simvastatin had lower low-density lipoprotein cholesterol levels by 3 months (adjusted mean difference −0·83 (95 per cent c.i. −1·4 to −0·22) mmol/l; P = 0·009). Median adherence to medication was greater than 90 per cent between 3 and 12 months' follow-up. Adverse events were similar between the groups. Quality-of-life data were complete for 98·3 per cent of questionnaire items. Cardiovascular disease, diabetes and aspirin use were more prevalent in the non-randomized group, whereas tumour site, stage and grade were similar between groups. Survival estimates were imprecise. Conclusion: This RCT supports the conduct and informs the design considerations for a future phase III trial of adjuvant statin therapy in patients with OAC. Registration number: ISRCTN98060456 (http://www.isrctn/com ).